Water-Energy-Food Nexus Review for Biofuels Assessment - Gazal, Abass A.; Jakrawatana, Napat; Silalertruksa, Thapat; Gheewala, Shabbir H. (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
The appropriate use of limited natural resources for generating basic human needs such as energy, food, and water, is essential to help the society function efficiently. Hence, a new approach called nexus is being considered to resolve the effects of intrinsic trade-offs between the essential needs. A review of different methods and frameworks of the water-energy-food nexus was done in this article to give a detailed repository of information on existing approaches and advocate the development of a more holistic quantitative nexus method. Assessing biofuels under the water-energy-food nexus perspective, this review addresses the sustainability of bioenergy production. The results show the countries that can sustainably produce first-generation biofuels. Only a few methods have varied interdisciplinary procedures to analyse the nexus, and more analytical software and data on resource availability/use are needed to address trade-offs between these interacting resource sectors constituting the nexus. Also, â€œlandâ€ is suggested as an additional sector to consider in future studies using both the nexus index and life cycle assessment methodology. The review reveals that to tackle composite challenges related to resource management, cross-disciplinary methods are essential to integrate environmental, socio-political facets of water, energy, and food; employ collaborative frameworks; and seek the engagement of decision-makers.